ADVANCED DETECTION IN BIOMEDICAL DIAGNOSTICS (2025)
Advanced Detection in Biomedical Diagnostics  is an initiatives from the members of Advanced Diagnostics and Progressive Human Care (DIAGNOSTICS) Research Group in Universiti Teknologi Malaysia that aim to brings together a range of emerging techniques that are reshaping modern biomedical analysis. The book highlights new methods for understanding human tissues and physiological processes, including the use of convolutional neural network (CNN) models to support early breast cancer detection through accurate pectoral muscle segmentation. It also explores infrared thermal imaging for studying brown adipose tissue (BAT) and examines how dietary habits influence key metabolic markers. The discussion extends to the regulated talk test (TT) and its potential as a dependable measure of exercise intensity in cardiac rehabilitation. Other chapters introduce a mobile application designed for wound assessment that tracks temperature, oxygen and pH levels, as well as studies that use thermography to analyse breathing patterns and to identify cardiorespiratory exercise intensity with greater precision. Clear, informative and forward-looking, this book is a valuable reference for researchers, clinicians and biomedical engineers who are working to advance diagnostic practices in healthcare.